A highly active and thermally stable 6, 13-dihydro-6, 13-ethanopentacene-15, 16-diimine nickel(ii) complex as catalyst for norbornene polymerization. Issue 82 (9th November 2017) - Huo, Ping; Li, Jingbo; Liu, Wanyun; Mei, Guangquan; He, Xiaohui
Abstract : A nickel catalyst with polycyclic aromatic systems on the backbone exhibits good thermal stability and high activity in norbornene copolymerization. Abstract : The 6, 13-dihydro-6, 13-ethanopentacene-15, 16-diimine nickel(ii ) complex was synthesized and characterized. The nickel complex exhibited high activity toward the homopolymerization of norbornene and copolymerization of norbornene with 5-norbornene-2-carboxylic acid methyl ester in the presence of B(C6 F5 )3 . It was observed that the nickel catalyst with large steric hindrance from polycyclic aromatic systems on the backbone was found to exhibit good thermal stability and afford high incorporation of polar monomers in norbornene copolymerization.